2018
DOI: 10.2298/abs180106026l
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of putative sclerotia maturation-related gene expression in Rhizoctonia solani AG1-IA

Abstract: Rhizoctonia solani AG1-IA (R. solani AG1-IA) is a major soil-borne fungal pathogen of maize that causes significant yield losses in all maize-growing regions worldwide. The sclerotium produced by R. solani AG1-IA can overwinter in grass roots or diseased plants and infect crops the following year. The molecular mechanism underlying sclerotium formation in R. solani is poorly understood. In this study, we constructed the cDNA library of the R. solani AG1-IA pathogenic strain WF-9, from which 329 high-quality ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Specifically for R. solani , previous studies showed fewer sclerotia were produced when cultured on the hydroxyl radial scavenger-amended or ascorbic acid-amended media [25, 26]. Consistently, exogenous application of H 2 O 2 resulted in more sclerotia formation [27–29], and the application of the catalase inhibitor aminotriazole resulted in increased sclerotia formation [27]. In addition, a sclerotia-forming R. solani isolate accumulated and secreted more H 2 O 2 than a non-sclerotia-forming isolate, suggesting that H 2 O 2 may be the key ROS for initiating sclerotia formation [23].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Specifically for R. solani , previous studies showed fewer sclerotia were produced when cultured on the hydroxyl radial scavenger-amended or ascorbic acid-amended media [25, 26]. Consistently, exogenous application of H 2 O 2 resulted in more sclerotia formation [27–29], and the application of the catalase inhibitor aminotriazole resulted in increased sclerotia formation [27]. In addition, a sclerotia-forming R. solani isolate accumulated and secreted more H 2 O 2 than a non-sclerotia-forming isolate, suggesting that H 2 O 2 may be the key ROS for initiating sclerotia formation [23].…”
Section: Introductionmentioning
confidence: 73%
“…Sclerotia are not only the survival structures to overcome environmental stresses, but also the primary and/or secondary inocula to initiate a disease cycle for many plant-pathogenic fungi. In particular for R. solani, the amount of sclerotia has been reported to be positively corelated with disease incidence in rice fields [104,105], and several studies have applied proteomic, metabolomic and transcriptomic approaches to understand sclerotia development of R. solani [28][29][30][31][32][33]106]. However, field isolates could produce sclerotia with various numbers and sizes, and whether or not the sclerotia-forming capability is influenced by genetic effects remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation